1976
DOI: 10.1007/bf01405860
|View full text |Cite
|
Sign up to set email alerts
|

On the nature of brain stem disorders in severe head injured patients

Abstract: The results of electro-oculographic recordings made after caloric vestibular stimulation (C.O.G.) in severe head injured patients are discussed. It was found that: 1. The C.O.G. correlates with the state of consciousness of the patients. 2. The rate of improvement of the C.O.G. correlates with the rate of the clinical improvement. 3. A prediction of the duration of unconsciousness can be made by repeated C.O.G. scores as well as by repeated scoring of the clinical state. 4. In all patients a paradoxical respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1978
1978
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Specific pathways discussed in literature include interconnections that originate within the midbrain, spinal cord, and frontal lobe. Using this model, damage to any of these interconnections could hypothetically result in abulia (36,37).…”
Section: Discussionmentioning
confidence: 44%
“…Specific pathways discussed in literature include interconnections that originate within the midbrain, spinal cord, and frontal lobe. Using this model, damage to any of these interconnections could hypothetically result in abulia (36,37).…”
Section: Discussionmentioning
confidence: 44%
“…Only three studies have investigated the use of vestibular stimulation in patients with severe brain injuries. Two early studies demonstrated a correlation between electrooculographic recordings after CVS and the state of consciousness, but the duration of this effect was unclear [ 206 , 207 ]. The third study showed time-locked behavioral improvements in two patients in a chronic MCS using a crossover design over 16–18 weeks of CVS and sham stimulation [ 208 ].…”
Section: Sensory Therapiesmentioning
confidence: 99%
“…Etiologies of AM ranged from infarction, tumors, ruptured aneurysnia, arteriovenous malformation, third ventricular cyst, hydrocephalus, encephalitis, meningitis and trauma (21). N-B disease is a rare cause of AM.…”
mentioning
confidence: 99%